2008
DOI: 10.7326/0003-4819-149-8-200810210-00005
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Neutral Protamine Lispro Insulin or Insulin Glargine to Oral Type 2 Diabetes Regimens for Patients with Suboptimal Glycemic Control

Abstract: Similar glycemic control occurred with the addition of NPL or glargine insulin to oral regimens in patients with poorly controlled type 2 diabetes. Hypoglycemia was similar in the 2 groups, but sample size limited the ability to make a definite safety assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 33 publications
5
43
4
Order By: Relevance
“…For both insulin treatment groups, postprandial excursions were similar at baseline and endpoint, indicating continued efficacy of exenatide BID. In studies where basal insulin was added to OAMs (without exenatide BID), T2D patients showed distinctly different SMPG profiles with greater post-breakfast and post-dinner glycaemic excursions 3,15,3032. Endpoint FPG values were substantially above target levels for both treatment group; however, FPG values were within the range observed in previous treat-to-target studies (5.6–7.4 mmol/l) 3,15,3032.…”
Section: Discussionmentioning
confidence: 99%
“…For both insulin treatment groups, postprandial excursions were similar at baseline and endpoint, indicating continued efficacy of exenatide BID. In studies where basal insulin was added to OAMs (without exenatide BID), T2D patients showed distinctly different SMPG profiles with greater post-breakfast and post-dinner glycaemic excursions 3,15,3032. Endpoint FPG values were substantially above target levels for both treatment group; however, FPG values were within the range observed in previous treat-to-target studies (5.6–7.4 mmol/l) 3,15,3032.…”
Section: Discussionmentioning
confidence: 99%
“…Diamant et al10 defined it as an episode between bedtime and breakfast. Esposito et al11 defined it as an episode between bedtime and being awake in the morning. Raskin et al12 defined nocturnal hypoglycemia as an episode between 11 pm and 8 am.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in patients starting on once-daily insulin showed a mean insulin glargine dose of 57 +/− 15 units [24]. A meaningful decrease would be a difference of at least 14 units.…”
Section: Methodsmentioning
confidence: 99%